Infinity crusade (1993), volume 1 ebook - Starlin, Jim (Infinity Crusade (1993), 2013)
Collects Infinity Crusade #1-3, Warlock Chronicles #1-3 & Warlock and the Infinity Watch #18-19. The Goddess has come. Captain America and Spider-Man are on her side; Thanos and Mephisto stand against her. So how can she be the bad guy? It's the Fantastic Four, the X-Men, the Avengers and more split by a universal crisis...of faith!